2013
DOI: 10.1002/cne.23233
|View full text |Cite
|
Sign up to set email alerts
|

Regional astrogliosis in the mouse hypothalamus in response to obesity

Abstract: Obesity is associated with chronic low-grade inflammation in peripheral tissues, which contributes to the development of comorbidities such as insulin resistance and cardiovascular disease. While less extensively characterized, obesity also promotes inflammation in the central nervous system (CNS) and the consequences of this inflammation for CNS function are only beginning to be examined. In response to CNS insults such as inflammation, astrocytes undergo a process of hypertrophy and hyperplasia known as reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
124
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(133 citation statements)
references
References 42 publications
(74 reference statements)
9
124
0
Order By: Relevance
“…Our findings that HFD consumption leads to increases in the number and size of the cell bodies of Iba-1-positive microglia, as well as increases in gene expression and staining for the astrocytic marker, GFAP, within the ARC are consistent with these previously-published studies. Furthermore, there is also evidence that GFAP immunoreactivity becomes elevated within the other specific nuclei of the hypothalamus, including the PVN of genetically and diet-induced obese female mice [38], which is consistent with our findings that GFAP mRNA and immunoreactivity are also elevated within the PVN.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings that HFD consumption leads to increases in the number and size of the cell bodies of Iba-1-positive microglia, as well as increases in gene expression and staining for the astrocytic marker, GFAP, within the ARC are consistent with these previously-published studies. Furthermore, there is also evidence that GFAP immunoreactivity becomes elevated within the other specific nuclei of the hypothalamus, including the PVN of genetically and diet-induced obese female mice [38], which is consistent with our findings that GFAP mRNA and immunoreactivity are also elevated within the PVN.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have ascertained that the level of GFAP, which is largely expressed in astrocytes, is increased in specific brain regions in response to various threats to the internal milieu of the brain [13, 37, 38]. Figures 4 and 5 depict the extent to which maintenance on a HFD for 8 wks impacts immunostaining for this astrocytic marker within the SFO, ARC, PaPVN, PeVN, PVN, and DMH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GFAP was detected using previously described methods 70 . Incubation with primary antibody - 1:1,000 anti-GFAP (Cat.#MAB360, Millipore, Bedford, MA) diluted in blocking buffer (5% milk, TBS-0.1% Tween 20), occurred overnight at 4°C with shaking.…”
Section: Methodsmentioning
confidence: 99%
“…Relevant to brain functions and behavior, the chronic low-grade inflammatory state that characterizes obesity and related metabolic disorders manifests also in the central nervous system (CNS). In the brain, cytokines are released by glial cells, including astrocytes and microglia, and experimental studies in rodents with diet-induced obesity show an increase in the number of microglial cells with a shift towards a proinflammatory profile [14] together with a recrudescence of activated astrocytes in the CNS [15]. Finally, it was recently shown that peripheral immune cells are also recruited into the CNS in obese rats fed with a high-fat diet [16].…”
Section: Chronic Low-grade Inflammation In Metabolic Disordersmentioning
confidence: 99%